Model Code and Data for "Assessing the Efficiency Implications of Renewable Fuel Policy Design in the United States" - Zhong, Jia; Khanna, Madhu (University of Illinois at Urbana-Champaign, 2022)
This dataset contains model code (including input data) to replicate the outcomes for "Assessing the Efficiency Implications of Renewable Fuel Policy Design in the United States".

The model consists of:
(1) The replication codes and data for the model. To run the model, using GAMS to run the "Models.gms" file.
Keywords: Renewable Fuel Standard; Nested structure; cellulosic waiver credit; RIN